OUTCOME AND ETIOLOGY OF NON TRAUMATIC COMA IN INTENSIVE CARE UNIT CHILDREN - WAJDAN, A; SALEEM, M; ZAFAR, MS; BASHIR, R; SHEIKH, S; HOORAIN, . (Biological and Clinical Sciences Research Journal, 2023)
The objective of this study was to analyze the clinical signs, outcomes, and causes of non-traumatic coma (NTC) in the pediatric ICU. The study was conducted retrospectively in the pediatric ICU of Nishtar Medical Hospital, Multan, from January 2021 to January 2022. The study included 140 children aged between 1 month and 14 years who were admitted to the ICU. The presenting symptoms were categorized as organ-specific, central nervous system (CNS), and non-CNS related. The causes of NTC were classified as infectious, metabolic, epilepsy, accidents, intoxication, shunt dysfunction, and others. The outcome was assessed based on the neurological state of the patients at the time of discharge or death. The results showed that out of the 140 patients, 57 (40.7%) were under two years old, 56 (40%) were between 2-6 years, and 27 (19.2%) were between 6-14 years. The children under two years old had higher systemic manifestations compared to other age groups. The most common causes of NTC were infections (32.1%) and epilepsy (28.5%). Congenital etiology and infections were significantly higher in children under two years compared to other groups, while intoxications and accidents were more common in children aged between 2-6 years. Epilepsy was more common in children over six years. Out of the 140 patients, 120 survived and 20 died. Among the 120 surviving patients, 8 had mild disability, 15 had moderate disability, 17 had severe disability, and 80 were normal at the time of discharge from the PICU. Mortality and etiology were significantly associated. In conclusion, infectious etiology is the most common cause of NTC. Infections and accidents are associated with the highest mortality rate. Children below two years have major systemic presentations at the time of PICU admission.